TanDEM-X Global DEM Quality Status and Acquisition Completion - Braeutigam, B.; Bachmann, M.; Schulze, D.; Tridon, D. Borla; Rizzoli, P.; Martone, M.; Gonzalez, C.; Zink, M.; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Symposium (IGARSS), 2014)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an interferometric SAR mission flying two radar satellites in close orbit formation. Its primary goal is the production of a homogeneous global digital elevation model (DEM) of unprecedented accuracy. Since 2010 all land surfaces have been mapped at least twice and difficult terrain even up to four times. While data acquisition for the DEM generation will be concluded in August 2014 it is expected to complete the processing of the global DEM by the end of 2015. This paper gives a status update on the current acquisition planning and presents quality results from a huge data base of more than 400,000 single DEM scenes and 1700 final DEM products.
DLR Import::2019-04-03
Keywords: Digital Elevation Model (DEM); Interferometry; Synthetic Aperture Radar (SAR)